PRINCIPLES OF QUALITY MANAGEMENT AND THE BENEFITS OF THEIR APPLICATION IN EDUCATION SECTORS (Journal of Pharmaceutical Negative Results, 2022)
TQM practices are important to provide customer satisfaction by improved product performance and sustained towards the organizational goal. The objective of this study was to analyze the relationship between TQM practices, process innovation and employee performance. In this study, six critical success factors of TQM have been identified namely customer focus, leadership, training, teamwork, communication, and top management. Based on thorough literature review, employee performances have been measured by two constructs which are job satisfaction and workplace environment.The results revealed that not all TQM practices enhanced production workers’ job satisfaction. Only organization culture and teamwork showed a positive relationship with the production workers’ job satisfaction.